Inverted stereotypes in the reflective-collaborative training of Portuguese foreign language teachers exam - Dutra, Anelise Fonseca (The ESPecialist, 2024)
This article presents the results of a training course for teachers of Portuguese as a Foreign Language in which there is no gap between the dichotomies of theory/practice and teacher/researcher (Wallace, 2001). This training values reflexive-collaborative work (Schon, 2000; Dutra; Mello, 2004) and its main objective was to analyze how this work related to intercultural education helps the teacher to develop a critical view of himself/herself as a Brazilian teacher and of the foreign students. As a methodology, we used the recording of classes and the notes that were taken for discussions in the collaborative sessions. One of the topics that emerged from the analyzes of the practice of the teachers were the stereotypes presented not only by the students, but mainly by the teachers themselves (Schneider, 2005; Borghetti, 2013 e McFarlane, 2014). As a result, we can point to the fact that our discussions led the teachers, at first, to become aware of their preconceived ideas and of the posture they assumed in class motivated by these prejudices (Maldonado-Torres, 2007; Quintero, 2019), thus leading them to rethink their beliefs and values and modify their actions.